Enigmatic Weak D antigen: An Experience in a Tertiary Care Hospital of East Delhi - Gupta, Anshu (J Clin Diagn Res, 2016)
INTRODUCTION: The Rh blood group system is one of the most polymorphic and immunogenic blood group systems in humans. The expression of Rh blood group antigen is complex, among that Rh-D antigen is the most important antigen because of its immunogenicity. It is easy to detect D antigen in most of the cases. Sometimes, variable expression of Rh-D antigen leads to presence of weak forms. Weak D reacts variably with anti D sera and poses a problem in blood banking. Molecular genetics of Rh-D revealed that weak D antigen is a Rh-D phenotype that possesses less numbers of complete D antigens on the surface of red blood cells. AIM: Present study was carried out to study weak D positivity in a tertiary neuropsychiatry hospital of East Delhi for compatibility testing in blood transfusion, to assess the implications and need of weak D testing and for population genetics study. This study tried to observe pattern of weak D antigen in four broadly classified religious communities also (Hindus, Muslims, Sikhs and Christians). MATERIALS AND METHODS: This was a two years prospective hospital based study including patients as well as donors. All patients were tested for Rh-D factor by commercially available monoclonal anti-D sera. The individuals who were found negative with anti-D were further investigated for weak D antigen by using indirect antiglobulin test (IAT) by tube as well as gel card technique. RESULTS: The results were compiled by using SPSS software version 21.0 and Microsoft excel. Among 3619 cases, 3502 (96.7%) were Rh-D factor positive while 117(3.2%) were Rh D factor negative. Among these 117 Rh-D negative cases, 9 (7.6% out of total Rh-D negatives and 0.25% out of total samples) were weak D positive and 108(2.98%) were actually D negative individuals after IAT. Weak D positivity showed a slight predominance in females (55.5%). As per broad religious communities, weak D antigen was found in Hindus only and not observed in Muslims, Sikhs and Christians. In weak D positive individuals, B phenotype (0.43%) was found to be most common followed by A (0.26%) and O (0.2%). CONCLUSION: Considerably high frequency of weak D antigen was noticed in study samples of this hospital. With this data based information, it is felt worthwhile to perform weak D testing routinely of those individuals who are negative with saline anti-D to prevent possibility of haemolysis and for efficient blood transfusion practices by making compatible blood available.